Desiccation Tolerance in the Antarctic Moss Sanionia Uncinata - Zuniga-Navarro, G; Kohler-Campos, H; Pizarro-Rojas, M; Contreras-Arredondo, R (NLM (Medline), 2019)
BACKGROUND: One of the most extreme environments on our planet is the Maritime Antarctic territory, due to its low-water availability, which restricts the development of plants. Sanionia uncinata Hedw. (Amblystegiaceae), the main colonizer of the Maritime Antarctic, has effective mechanisms to tolerate this environment. It has been described that the tolerance to desiccation is mediated by the hormone abscisic acid (ABA), antioxidants systems, accumulation of compatible solutes and proteins of the late embryogenesis abundant (LEA). However, to date, these mechanisms have not been described in S. uncinata. Therefore, in this work, we postulate that the tolerance to desiccation in the Antarctic moss S. uncinata is mediated by the accumulation of ABA, the osmolytes proline and glycine betaine, and dehydrins (an LEA class 11 proteins). To demonstrate our hypothesis, S. uncinata was subjected to desiccation for 24 h (loss in 95% of water content), and the effects on its physiological, photosynthetic, antioxidant and biochemical parameters were determined. RESULTS: Our results showed an accumulation of ABA in response to water loss, and the activation of protective responses that involves an increment in levels of proline and glycine betaine, an increment in the activity of antioxidant enzymes such as SOD, CAT, APX and POD, and the accumulation of dehydrins proteins. CONCLUSION: The results showed, suggest that S. uncinata is a  desiccation-tolerant moss, property mediated by high cellular plasticity regulated by ABA.